BUILDING A DATA-DRIVEN FUTURE: A LITERATURE REVIEW ON DATA CULTURE AND BUSINESS ANALYTICS ADAPTION - Patil, Harshal; Kulkarni, Abhay (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The capacity of firms to extract value from data is evolving into a matter of strategic importance in an increasingly digitized world. This paper utilizes a systematic literature review to examine the complex interplay between data culture and the adaption of business analytics, in different contexts of organizations. Although data-driven technologies are nearly ubiquitous, many firms still struggle to develop a cohesive culture to meaningfully integrate analytics. The study's objectives are to (1) bring together the existing literature on data culture and adaption of business analytics, (2) examine the influences of enablers and barriers such as leadership, digital maturity, and data literacy, and (3) establish theoretical frameworks and possible research gaps for future studies. In this study, were systematic - examining peer-reviewed journals and conference proceedings and academic databases such as Scopus, IEEE, SSRN, etc. Narrative synthesis and thematic analysis were used to address the influences of organizational, technological, environmental, and human resources and capital factors along established models; Technology-Organization-Environment (TOE), Dynamic Capabilities Theory, and the Diffusion of Innovations (DOI) theory. Research findings support strong leadership support, organizational cross-member collaboration, accessibility to data, and analytics competence will create critical factors in the successful adoption of business analytics. Our findings also indicate that resistance to change, skills deficit, and strategic misalignment are accompanying challenges. The review identifies a number of gaps in empirical research across specific industries, calling for multidisciplinary, longitudinal research that integrates behavioral and technological component. Actionable strategic implications are made for managers, IT professional, and human resource leaders to assist with cultural change within a data focused organization. Finally, the paper emphasizes that developing a balanced and inclusive data culture will assist organizations in leveraging benefits of business analytics, and creating a competitive advantage in the digital age.